Creativity 360 degrees : exploring the dynamics of the creative industries in southeast Europe - Holy, Mirela; Budak, Jelena; Medić, Rino (Emerald Publishing Limited, 2025)
Globally recognised and endorsed by EU policies, creative industries play a pivotal role in fostering cultural diversity, social cohesion, and technological innovation. Further, they play a key role in national and regional economies. Despite this, Southeastern Europe falls behind the rest of Europe in implementing sustainable policies and establishing supportive ecosystems for creative industries. Nevertheless, the region boasts distinctive strengths and opportunities. Creativity 360 Degrees offers a comprehensive examination of the creative industries sector in Southeast Europe, spanning countries such as Albania, Bosnia and Herzegovina, Bulgaria, Croatia, Greece, Kosovo, Montenegro, North Macedonia, Romania, Serbia, and Slovenia. Through insightful contributions, chapters delve into the way creative industries drive entrepreneurship, attract investment, and stimulate local economies. Authors explore the creative industries' connection to urban development, gentrification, and renewal, while also addressing their cultural impact on shaping identities and values through the production, consumption, and dissemination of various cultural products. This work investigates the integration of creative industries with technology and digital media, alongside education and workforce development. Delivering comprehensive insights into the multifaceted impacts of creative industries on culture, society, and the economy, this work is relevant for scholars and researchers in fields such as cultural studies, urban development, economics, sociology, and public policy.